Validation of a physically-based solid oxide fuel cell anode model combining 3D tomography and impedance spectroscopy - Bertei,A; Ruiz-Trejo,E; Tariq,F; Yufit,V; Atkinson,A; Brandon,NP (International Journal of Hydrogen Energy, 2016)
This study presents a physically-based model for the simulation of impedance spectra in solid oxide fuel cell (SOFC) composite anodes. The model takes into account the charge transport and the charge-transfer reaction at the three-phase boundary distributed along the anode thickness, as well as the phenomena at the electrode/electrolyte interface and the multicomponent gas diffusion in the test rig. The model is calibrated with experimental impedance spectra of cermet anodes made of nickel and scandia-stabilized zirconia and satisfactorily validated in electrodes with different microstructural properties, quantified through focused ion beam SEM tomography. Besides providing the material-specific kinetic parameters of the electrochemical hydrogen oxidation, this study shows that the correlation between electrode microstructure and electrochemical performance can be successfully addressed by combining physically-based modelling, impedance spectroscopy and 3D tomography. This approach overcomes the limits of phenomenological equivalent circuits and is suitable for the interpretation of experimental data and for the optimisation of the electrode microstructure.